Custom Law Regulations for Foreign Traders in the Kingdom of Buton: A Study Based on Manual Texts "Sarana Sabandara" or "Sarana Jurubasa" - Niampe, La; Syahrun; Sensu, La; Aso, La; Laniampe, Hasdairta (Advances in Social Sciences Research Journal, 2023)
This research is entitled "Customary Law Regulations for Foreign Traders in the Kingdom of Buton". This research aims to describe and analyze the customary law regulations for foreign traders in the Kingdom of Buton as contained in the texts of "Sarana Sabandara" or "Sarana Jurubasa". Through philological studies, it can be seen that the texts of "Sarana Sabandara" or "Sarana Jurubasa" describe several customary law regulations in the Buton Kingdom that foreign traders must know and obey in the territory of the Buton kingdom. According to Buton’s customary law regulations, officials authorized to take care of foreign traders in the Buton Kingdom were Sabandara officials and Jurubasa officials.